Development of Artistic Supervision Based Digital Reflection Log in Improving SMP Teachers’ Pedagogical Competence - Afrinawati, Fitria; Rusdinal, Rusdinal; Marsidin, Sufyarma; Rifma, Rifma (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
his study aimed to develop an artistic supervision-based Digital Reflection Log to improve the pedagogical competence of junior high school teachers by evaluating its validity, practicality, and effectiveness. This study employed a Research and Development (R&D) approach using the ADDIE model. The development process resulted in a web-based Digital Reflection Log platform, a supervision guidebook, and pedagogical competence assessment instruments. Expert validation indicated that the developed product was categorized as very valid, while the practicality and effectiveness tests yielded scores of 85.1% and 81.7%, respectively, indicating that the product is very practical and very effective. The findings suggest that integrating artistic supervision with a Digital Reflection Log provides an effective and practical approach to supporting reflective practice and the continuous improvement of teachers' pedagogical competence.